TRANSFORMASI PEMBIAYAAN BERBASIS GREEN FINANCING PADA BANK SYARIAH INDONESIA PERSPEKTIF HUKUM ISLAM - Ridwan, Muhammad; Hidayah Harahap, Purnama (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
This article aims to examine the application of green financing-based financing at Bank Syariah Indonesia (BSI) from an Islamic law perspective. This research includes library research, which interprets the concepts contained in green financing. Data sources in this research are books, Bank Syariah Indonesia reports, articles and relevant manuscripts or documents. The results of this research show that the application of green financing at Bank Syariah Indonesia has increased from the previous year. This reached IDR 52.6 trillion or 23.77% based on total BSI financing. This green financing program has a positive impact on sustainable economic development in Indonesia, especially the contracts used based on Islamic principles. Review of Islamic law regarding green financing, namely Hifzh al-Maal (Maintenance of Assets), Hifzh al-Nafs (Care of the Soul), Hifzh al-Nasl (Care of Offspring), Hifzh al-'Aql (Care of the Mind) and Hifzh al -Din (Religious Maintenance) has been carried out based on legal provisions.